Thiamine Ameliorates Diabetes-Induced Inhibition of Pyruvate Dehydrogenase (PDH) in Rat Heart Mitochondria: Investigating the Discrepancy Between PDH Activity and PDH E1α Phosphorylation in Cardiac Fibroblasts Exposed to High Glucose - Yuka Kohda; Masashi Umeki; Tatsuji Kono; Fumio Terasaki; Hitoshi Matsumura; Takao Tanaka (Elsevier, 2010)
The activity of pyruvate dehydrogenase (PDH) is reduced in diabetic patients. Phosphorylation of the PDH E1α subunit by PDH kinase contributes to the suppression of PDH activity. PDH requires thiamine as a coenzyme. We investigated the exact mechanism of diabetes-induced PDH inhibition, and the effect of thiamine in both in vivo and in vitro experiments. Treatment of rats with thiamine significantly, although partially, recovered streptozotocin (STZ)-induced reductions in mitochondrial PDH activity. Nevertheless, we found that PDH E1α phosphorylation in the thiamine-treated STZ group was perfectly diminished to the same level as that in the control group. STZ treatment significantly caused enhancements of the expression of O-glycosylated protein in the rat hearts, which was decreased by thiamine repletion. Next, the rat cardiac fibroblasts (RCFs) were cultured in the presence of high glucose levels. Thiamine dramatically recovered high glucose-induced PDH inhibition. High glucose loads did not alter the phosphorylated PDH E1α. PDH inhibition in RCFs was not accompanied by an increase in the PDH E1α phosphorylation. The O-glycosylated protein was markedly increased in RCFs exposed to high glucose, which was inhibited by thiamine. These results suggest that thiamine ameliorates diabetes-induced PDH inhibition by suppressing the increased expression of the O-glycosylated protein. The O-glycosylation of PDH E1α may be involved in the regulation of the PDH activity. Keywords:: thiamine, pyruvate dehydrogenase (PDH) activity, phosphorylated PDH E1 α, O-glycosylated protein, diabetic rat heart